The feeding ecology of curlew sandpipers Calidris ferrugineol in the South - Western Cape, South Africa - Puttick, Gillian Margaret (Department of Biological Sciences, 2023)
Spatial and temporal changes in the distribution of food organisms potentially available to curlew sandpipers Calidris ferruginea at Langebaan Lagoon (33°s, 18°E), South Africa, are described for the period February 1974 - March 1975. Seasonal changes in the diet of curlew sandpipers foraging in the intertidal sandflats and marshes were studied, and the food taken by male and female, and immature and adult, birds was compared. The daily and seasonal activity of curlew sandpipers was monitored during March 1974 - March 1975 and this also provided information on the birds' foraging behaviour and foraging techniques, their use of microhabitat and their foraging related to shore level. Variations during the austral summer in the density and the foraging of curlew sandpipers related to the density of their prey was investigated in the light of Royama's (1971) theory of profitability. The foraging behaviour and spatial distribution of foraging male and female curlew sandpipers at Kommetjie (34 o8°s, 18 19°E) was compared, since curlew sandpipers show sexual dimorphism with females having-longer culmens. The energy requirements and energy intake of curlew sandpipers at Langebaan Lagoon are described. The gross annual production of the benthic invertebrates potentially available to the birds was estimated, as well as the birds' impact on this.